Predicting therapeutic efficacy of oral rehydration salts in children with vasovagal syncope - Du, Xiaojuan; Tao, Chunyan; Li, Xueying; Du, Junbao; Liao, Ying; Jin, Hongfang (Frontiers in Pediatrics, 2023)
Objective：This study was designed to develop an easy-to-perform and inexpensive measure to predict efficacy of oral rehydration salts (ORS) for children with vasovagal syncope (VVS). Materials and Methods: Totally 97 children diagnosed as VVS and treated with ORS for a median of 3 months at Peking University First Hospital, China were enrolled and followed up. Demographic data, clinical hemodynamic parameters and variables related to red blood cells were collected at the baseline. On the basis of changes in symptom scores after treatment, participants were divided into effective or ineffective groups at the end of the follow-up. Logistic regression analysis was used to investigate parameters related to therapeutic efficacy of ORS and a predictive model of ORS effectiveness was created. The predictive efficiency was evaluated using receiver operating characteristic curve (ROC). The accuracy/consistency was evaluated by Hosmer-Lemeshow test and calibration curve. Internal validation was done using bootstrap approach. Results: Totally 97 pediatric participants were included in the study and 4 (4.1%) were lost during the follow-up. ORS therapy was effective in 46 children and ineffective in 47 children. Children in the effective group had higher baseline red blood cell count, hemoglobin, and hematocrit than those in the ineffective group (p < 0.01). Through logistic regression analysis, the baseline hematocrit and body mass index (BMI) were included in predictive model for the response to ORS treatment. The predictive efficacy of ORS showed an area under the curve (AUC) of 0.77 (p < 0.01). The predicted probability cutoff value of 0.5 was found to be optimal, with a resulting sensitivity of 67.4% and specificity of 80.9%. In Hosmer-Lemeshow test, p value was 0.75, and the calibration plot showed a good model fitness. Internal validation was performed using bootstrap (n = 1000), showing 95% confidence interval (CI): 0.67-0.86. Conclusion: Hemoglobin combined with BMI was useful for predicting the therapeutic efficacy of ORS in children with VVS.